Manejo da água associado à cobertura de canteiros no controle de manchas foliares em mudas de eucalipto - Camargo, Mariane Bueno de (2014)
Xanthomonas species are responsible for diseases that can defoliation of plants still in the juvenile stage in various crops. Several are the pathogenic species, which have high degrees of specificity and some are divided into several pathovars, a kind of designation based on their hosts. Commonly the Eucalyptus spp., planted throughout Brazil, and may limit the use of genetic materials susceptible, since they induce leaf spots causing their defoliation and consequently limiting their potential productivity. This study aimed to evaluate the efficiency of antibiotics and fungicides currently used in agriculture aimed at inhibiting the growth "in vitro" of phytopathogenic bacteria isolates in Eucalyptus spp., in the nursery and field, as well as to assess the effects of management water on the severity of bacterial spot in clonal seedlings of E. urophylla x E. grandis tree nursery. For laboratory evaluations were used to filter paper soaked for eight active ingredients tested and available in Petri dishes containing the inoculum Xanthomonas axonopodis, originating from plants infected with the disease in the tree nursery where the second phase of the experiment was installed . Assessments were made through measurements of the inhibition zones Xae pv. eucalypti subjected to 8 repetitions, totaling 64 analysis, resulting in the total inefficiency of all was tested in control Xae pv. eucalypti in the laboratory, not being then subjected to field control test. The second part of the experiment is related to water management in forest nursery for the control of disease on seedlings newly outputs the hardening house growing area, assessed in two different seasons (spring and summer), higher incidence of periods of disease in nurseries. The main management method was full and partial coverage of the site where the plants were ready. This reduction in frequency of availability of water on the leaves of the Eucalyptus hybrid showed satisfactory and effective results for disease control while also providing increase in seedling growth between 22-25%, requiring less waiting time in the nursery of these plants for planting field confirming the theory and use of the recommendations of the integrated control of pests and diseases in forestry.